2004
DOI: 10.1086/381560
|View full text |Cite|
|
Sign up to set email alerts
|

Premature Myocardial Infarction Novel Susceptibility Locus on Chromosome 1P34-36 Identified by Genomewide Linkage Analysis

Abstract: The most frequent causes of death and disability in the Western world are atherosclerotic coronary artery disease (CAD) and acute myocardial infarction (MI). This common disease is thought to have a polygenic basis with a complex interaction with environmental factors. Here, we report results of a genomewide search for susceptibility genes for MI in a well-characterized U.S. cohort consisting of 1,613 individuals in 428 multiplex families with familial premature CAD and MI: 712 with MI, 974 with CAD, and avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
145
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(152 citation statements)
references
References 31 publications
3
145
4
Order By: Relevance
“…Five whole-genome scans for premature MI were identified in PubMed (Helgadottir et al 2004;Wang et al 2004;Broeckel et al 2002;Hauser et al 2004;Samani et al 2005). In these scans, overlapping of cases was not reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five whole-genome scans for premature MI were identified in PubMed (Helgadottir et al 2004;Wang et al 2004;Broeckel et al 2002;Hauser et al 2004;Samani et al 2005). In these scans, overlapping of cases was not reported.…”
Section: Resultsmentioning
confidence: 99%
“…The study by Broeckel et al (2002) consisted of 513 pedigrees with 944 affected individuals (Caucasians); 394 microsatellite markers and multipoint analysis were used. In the study by Hauser et al (2004) the genome scan was performed in 228 pedigrees mainly from a Caucasian population (93%); the number of affected individuals was not reported; the Wang et al (2004) (P values were used). In weighting, the studies by Broeckel et al (2002) and Hauser et al (2004) produced the least weight, with a weight factor w=0.15, and the study by Helgadottir et al (2004), with the most weight (w=0.28).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is of interest that there is other evidence of linkage of CAD to this region: a LOD score of 3.7 was reported in an isolated Finnish population 22 and a LOD score of 3.82 was found in the same region using a US cohort of MI patients. 7 In the Finnish study, 22 families were excluded when a proband was affected by familial hypercholesterolemia, whereas the US study 7 excluded all the subjects affected by hypercholesterolemia. Farrall et al 23 also found a LOD score 41 in the same region using a cohort from across four European countries.…”
Section: Discussionmentioning
confidence: 99%
“…4 -6 One way of resolving the problem of heterogeneity is to use a more restrictive definition of phenotype at recruitment or to separately analyse subsets of the study participants with more homogeneous disease characteristics. For example, Wang et al 7 reported significant evidence of linkage to a locus on chromosome 1 by considering subjects with myocardial infarction (MI), diagnosed by age 45 years in males or 50 years in females. Applying narrow criteria at recruitment involves strong assumptions about which phenotypic groups are likely to be genetically homogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…Although CAD can also rarely be inherited in a Mendelian fashion (predominantly in conditions leading to elevated LDL), this only accounts for a small proportion of incident cases [7], most of which are likely to be polygenic. Linkage studies of non-Mendelian CAD have provided some unbiased associations [8][9][10][11][12][13][14][15][16], even though these have conspicuously lacked reproducibility between cohorts. However, linkage studies will always suffer from poor statistical power and the lack of detailed genomic mapping provided by conventional microsatellite markers.…”
Section: Genome-wide Association Studies: Getting Closer To the Genetmentioning
confidence: 99%